Confined growth of Fe2O3 nanoparticles by holey graphene for enhanced sodium-ion storage. (May 2021) - Zheng, Cheng; Xu, Xiangcheng; Lin, Qiaowei; Chen, Yaowu; Guo, Zhu; Jian, Bangquan; Li, Na; Zhang, Haiyan; Lv, Wei
Abstract: Metal oxide/graphene hybrids are promising anode materials for sodium-ion batteries (SIBs). However, avoiding the overgrowth of the metal oxide nanoparticles (NPs) with high content and eliminating the blocking effect of graphene towards ion diffusion are still hard to achieve, lowering the active material utilization. Herein, we prepare a Fe2 O3 /holey graphene (FHG) anode for SIBs with enhanced electrochemical performance. The introduced hole edges and functional groups in holey graphene help adsorb Fe 3+ and anchor the formed NPs to avoid their aggregation through the formation of Fe–O–C bonds, effectively confining the growth of Fe2 O3 NPs and enhance their electrochemical activity. Besides, the holes on graphene facilitate the ion-transport to enhance the utilization of Fe2 O3 and decrease the ion-diffusion resistance. As a result, FHG shows the uniformly distributed NPs with around 30 nm with a high Fe2 O3 content of ∼73 wt%, and thus, the improved reversible capacity (923 mAh g −1 at 0.1 A g −1 ) and rate capability (318 mAh g −1 at 2 A g −1 ), much better than the Fe2 O3 /graphene hybrid without holes. This work demonstrates an effective method to improve the utilization and reaction kinetics of metal oxide, which can be extended to prepare the other hybrid materials for different applications. Graphical abstract: Image 1 Highlights: Holey graphene effectively confines the growth of Fe2 O3 nanoparticles on its surface. The holey structure and the small and uniform particle size ensure the high utilization of Fe2 O3 . The obtained hybrid for sodium-ion storage shows the high capacity and rate capability.